HUBUNGAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN - Hasmika, Hasmika; Sulistyarini, Sulistyarini; Utomo, Bambang Budi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this study is to determine the relationship of learning independence to the learning outcomes toward Pancasila and Civic Education subject on the students of class X IPS 3 of SMA Negeri 1 Pontianak. The method in this study is descriptive method with a form of relationship study (Interrelationship Studies). The population in this study were 30 students because this study took only one class.  The technique of Data collection in this study is Direct Observation Technique, Indirect Communication Technique (learning independence questionnaire), Documentary Study Technique (student test score data). The results of this study indicate that there is a relationship between learning independence to the learning outcomes toward Pancasila and Civic Education subject on the students of class X IPS 3 of SMA Negeri 1 Pontianak. It can be seen that the significance value is obtained at 0,000 or less than 0.05.   So it can be concluded that Ha is accepted and Ho is rejected. Therefore it can be concluded that there is a significant relationship between learning independence towards the learning outcomes of  Pancasila and Civic Education subject on the students of class X IPS 3 of  SMA Negeri 1 Pontianak. The conclusion of this study is learning independence has a significant relationship to the learning outcomes of  Pancasila and Civic Education subject on the students of class X IPS 3 of  SMA Negeri 1 Pontianak that is 7.6%. Keywords : Learning Independence, Student Learning Outcomes.